In the Heideggerian Tradition: Acontecimiento by Concha García - Martha LaFollette Miller (Studies in 20th & 21st Century Literature, 2012)
Critics Sharon Keefe Ugalde and Tina Escaja have called the poetry of Concha García “enigmatic,” “unique,” and “avant-garde.” Studies of her work to date tend to attribute the fragmentation and discontinuity of her poetic discourse to her rejection of phallologocentric language. While one of her work’s chief concerns is indeed her speaker’s sense of a radical difference and alienation based on gender, her poetry at the same time directs her reader’s attention to more general ontological considerations. Rather than clearly recounting the events of the life of her poetic protagonist, she rejects the distillations and simplifications that linear narration presupposes in order to explore the textures of being in the world—the moments of daily existence and the way in which what matters to the individual subject is actually experienced. Among the quotations García uses to introduce segments of her 2008 book Acontecimiento are several that can be linked to notions of authenticity in Heidegger’s Being and Time. This essay proposes to use Acontecimiento as a point of departure to examine the connections between García’s distinctive and at times enigmatic poetry and a particular view of time and place akin to Heidegger and his concept of Dasein. It anticipates that her incorporation of Heidegger, in its lucidity and eclecticism, will have postmodern characteristics that reflect the freshness of García’s poetic vision.
Keywords: Concha García; Acontecimiento; poetry; poetic discourse; ontology; ontological; gender; experience; existence; Heidegger; Being and Time; postmodern